Fungsi Komplementer Gender Dalam Keseimbangan Sistem Sosial Warga Kanekes - Muhamad Isyam Firdaus; Yusran Ilyas; syaripulloh; Nurlia Safitri; Azizah Nurazizah (PURBAWIDYA, 2026)
The Kanekes people demonstrate a complementary gender function system in which each gender fulfills distinct yet mutually dependent roles to sustain the overall social system balance. This study analyzes how complementary gender functions are constructed and maintained through the Sunda Wiwitan belief system. Using a historical method heuristics, source criticism, interpretation, and historiography and oral data from in-depth interviews. Findings show that Kanekes men and women carry out complementary functions: men handle agricultural labor and external representation, while women govern sacred seed management and household production. Both roles are grounded in the theological concepts of Ambu and Nyi Pohaci, rendering each function indispensable to the social system. This study's novelty lies in its integrative analysis of how sacred obligation and subsistence rationality together sustain gender complementarity a dimension underexplored in prior literature. The conclusion is that complementary gender functions constitute the primary mechanism for preserving the social balance of Kanekes, maintained through internalized customary norms across generations.